Liver transplant associated with paracetamol overdose: results from the seven‐country SALT study. (27th May 2015) - Gulmez, Sinem Ezgi; Larrey, Dominique; Pageaux, Georges‐Philippe; Bernuau, Jacques; Bissoli, Franco; Horsmans, Yves; Thorburn, Douglas; McCormick, P. Aiden; Stricker, Bruno; Toussi, Massoud; Lignot‐Maleyran, Séverine; Micon, Sophie; et al.
<x xml:space="preserve">Abstract</x> Aims Acute drug overdose, especially with paracetamol, may cause acute liver failure leading to registration for transplantation (ALFT). Population statistics and between‐country differences for ALFT related to overdose have been poorly described. The aim of the present study was to evaluate overdose ALFT in the multi‐country Study of Acute Liver Transplantation (SALT). Methods All adult overdose‐related ALFT, with or without suicidal intent, in France, Greece, Ireland, Italy, the Netherlands, Portugal and the UK between 2005 and 2007 were identified from liver transplant registries and hospital records. These were compared with whole‐country and per capita use of paracetamol. Results Six hundred cases of ALFT were identified in 52 of 57 eligible transplant centres, of which 114 involved overdose (72 intentional, 10 non‐intentional, 32 uncertain). Overdose represented 20% of all‐cause ALFT: Ireland 52%, UK 28%, France 18%, the Netherlands 8%, and Italy 1%. Overdose ALFT were mostly females (61%), mean age 33.6 ± 10.9 years. A total of 111 (97%) of the overdoses involved paracetamol. Event rates ranged from one ALFT for 20.7 tons of paracetamol in Ireland, to one for 1074 tons in Italy and one case in 60 million inhabitants over 3 years in Italy to one case in 286 000 inhabitants per year in Ireland. Per‐country event rates for non‐overdose ALFT exposed to paracetamol were between 2.5 and 4.0 per million treatment‐years sold. Conclusions Paracetamol overdose was found to represent one‐sixth of all‐cause ALFT. There was a 50‐fold difference in Europe in the rates of paracetamol overdose ALFT, and a 200‐fold difference per million inhabitants.